A fiatalok kollégiumi közösségbe való beilleszkedésének segítése - Princz, Enikő; Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2014)
Helping students adapt to the community of dormitories The literature I have studied provided a good background to map the mental and physiological background of the age bracket in question. My research revealed that family back-ground has a huge impact on an individual’s ability to adapt to new environments, to obey rules, and to solve problems. In a young person’s life peer groups play the most decisive role. A key factor for the adolescent population is leisure time, for which residence halls are supposed to offer proper programmes within their bounds.
Keywords: socialization; education in a residence hall; adapting; peer groups; adolescence; spending leisure time